A study on dynamic stress of planetary gear transmission in non-inertial system - Jing Wei; Miaofei Cao; Aiqiang Zhang; Hao Cheng; Bin Peng (Journal of Low Frequency Noise, Vibration and Active Control, 2023)
Considering the comprehensive effect of the internal non-inertial system of planetary gear transmission (PGT) and external non-inertial system of the body, combined with the modified Heywood formula and Hertz formula, a calculation model for the dynamic bending stress and contact dynamic stress of the PGT in a non-inertial system (NIS) is proposed. The stress non-inertial coefficients ( K NI ) describing the influence of the additional effects on the dynamic stress in the non-inertial system are defined. Additionally, the variation law of non-inertial coefficients under two typical non-inertial conditions of variable-speed horizontal flight and somersault motion was studied. The effect of gear installation and manufacturing errors on the non-inertial coefficients under two maneuvering conditions was analyzed. The results indicated that non-inertial coefficients increase with an increase in the maneuverability of the body, and the variable-speed horizontal flight and somersault motion have significant effects on the changing trend of non-inertial coefficients with the gear installation and manufacturing errors. Compared with the gear error, the effect of the NIS has a significant influence on the non-inertial coefficients.